2021
DOI: 10.3389/fonc.2021.588010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Microvascular Invasion of Hepatocellular Carcinoma Based on Contrast-Enhanced MR and 3D Convolutional Neural Networks

Abstract: Background and PurposeIt is extremely important to predict the microvascular invasion (MVI) of hepatocellular carcinoma (HCC) before surgery, which is a key predictor of recurrence and helps determine the treatment strategy before liver resection or liver transplantation. In this study, we demonstrate that a deep learning approach based on contrast-enhanced MR and 3D convolutional neural networks (CNN) can be applied to better predict MVI in HCC patients.Materials and MethodsThis retrospective study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…However, with increasing recognition of MVI and its prognostic value on surgical outcomes of HCC, preoperative MVI prediction systems for surgical decision making have become a hot topic in recent researches. In recent years, some studies have reported the possibility of imaging findings to predict the MVI of HCC (24)(25)(26)(27). However, it still has a limited capacity to detect MVI and the precise detection of MVI needs further histological identification (28).…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing recognition of MVI and its prognostic value on surgical outcomes of HCC, preoperative MVI prediction systems for surgical decision making have become a hot topic in recent researches. In recent years, some studies have reported the possibility of imaging findings to predict the MVI of HCC (24)(25)(26)(27). However, it still has a limited capacity to detect MVI and the precise detection of MVI needs further histological identification (28).…”
Section: Introductionmentioning
confidence: 99%
“…Although practice varies between treatment centers, many lines of evidence suggest that the best method for detection of liver metastases from CRC are computed tomography (CT) and magnetic resonance imaging (MRI) ( 9 ). For lesions with a diameter of less than 10 mm, MRI is a more sensitive modality than CT ( 10 , 11 ), and specifically in hepatobiliary MRI with specific contrast enhancers (such as gadoxetate), showing a higher accuracy of lesion detection ( 12 15 ). Many studies have investigated the optimal modality for imaging hepatic metastases, finding pooled sensitivity on a per-lesion basis of 88% for MRI, 74% for CT, and 79% for positron emission tomography/computed tomography (PET/CT) ( 9 , 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using DL based on preoperative CT showed a considerable e cacy (AUC: 0.906) in predicting MVI 45 . Two other independent studies using DCE-MRI and 3D Convolutional Neural Networks instead of CT images to predict MVI achieved an AUC of 0.931 and 0.926 respectively 46,47 .…”
Section: Discussionmentioning
confidence: 97%